Thermal sensation and comfort in transient conditions in hot-humid environment - Gital, Yakubu Yau (2016)
The study was conducted to identify affective and sensory responses observed as a result of hysteresis effects in transient thermal conditions consisting of warm-neutral and neutral-warm outside of a laboratory setting. Air-conditioned building interiors in hot/humid areas have resulted in thermal discomfort and health risks for people moving into and out of buildings. Reports have shown that the immediate change in air temperature can cause unexpected thermoregulation responses. Thermal Sensation Vote (TSV) and Thermal Comfort Vote (TCV) assessments as a consequence of moving through spaces with different thermal conditions were conducted in an existing single-story office in a hot-humid microclimate, maintained at an air temperature of 24°C. Subjective assessments consisting of sensations, preferences and thermal comfort votes were correlated against a steady state PMV model. Local skin temperatures on the forehead and dorsal left hand were included to observe physiological responses due to thermal transition. Sensory and affective responses as a consequence of thermal transition after travel from warm-neutralwarm conditions did not replicate the hysteresis effects of brief, slightly cool, thermal sensations found in previous laboratory experiments.